PENERAPAN PERMAINAN MEMANCING ANGKA UNTUK MENINGKATKAN KEMAMPUAN MENGENAL KONSEP BILANGAN PADA ANAK KELOMPOK A RAUDHATUL ATHFAL AL AMIN BONANGAN PAKIS MALANG (Jurnal Dewantara, 2019)
This research was conducted to find out the introduction of number concepts in group A children RA AL AMIN trough the application of numerical fishing games. This research is based on the results obtained from the initial observation obtained by the research her through interview with class educators and the results of RA AL AMIN group A children’s ability to recognize the concept of numbers are still in less criteria. The concept of child numbers only uses worksheets as media. This study was conducted on group A children in RA AL AMIN Bonangan Pakis Malang, emounting to seventeen students. The data collection techniques used were observation, interview and documentation. The results showed that the application of numerical fishing games can improve the ability of RA AL AMIN group children in recognizing the concept of numbers before the study only reached an average percentage of 23,56%. After conducting research with the application of fishing games the ability to recognize the concept of numbers in the first cycle reached an average percentage of 52,59% and the second cycle increased by 88,23%. Has reached the percentage of comprehension.